Changes and Clinical Consequences of Smoking Cessation in Patients With COPD: A Prospective Analysis From the CHAIN Cohort - Martínez-González, Cristina; Casanova, Ciro; de-Torres, Juan P; Marín, José M; de Lucas, Pilar; Fuster, Antonia; Cosío, Borja G; Calle, Myriam; Peces-Barba, Germán; Solanes, Ingrid; Agüero, Ramón; Feu-Collado, Nuria; et al. (Chest, 2018)
Despite the existing evidence-based smoking cessation interventions, chances of achieving that goal in real life are still low among patients with COPD. We sought to evaluate the clinical consequences of changes in smoking habits in a large cohort of patients with COPD. CHAIN (COPD History Assessment in Spain) is a Spanish multicenter study carried out at pulmonary clinics including active and former smokers with COPD. Smoking status was certified by clinical history and co-oximetry. Clinical presentation and disease impact were recorded via validated questionnaires, including the London Chest Activity of Daily Living (LCADL) and the Hospital Anxiety and Depression Scale (HADS). No specific smoking cessation intervention was carried out. Factors associated with and clinical consequences of smoking cessation were analyzed by multivariate regression and decision tree analyses. One thousand and eighty-one patients with COPD were included (male, 80.8%; age, 65.2 [SD 8.9] years; FEV , 60.2 [20.5]%). During the 2-year follow-up time (visit 2, 906 patients; visit 3, 791 patients), the majority of patients maintained the same smoking habit. Decision tree analysis detected chronic expectoration as the most relevant variable to identify persistent quitters in the future, followed by an LCADL questionnaire (cutoff 9 points). Total anxiety HADS score was the most relevant clinical impact associated with giving up tobacco, followed by the LCADL questionnaire with a cutoff value of 10 points. In this real-life prospective COPD cohort with no specific antismoking intervention, the majority of patients did not change their smoking status. Our study also identifies baseline expectoration, anxiety, and dyspnea with daily activities as the major determinants of smoking status in COPD. ClinicalTrials.gov; No. NCT01122758; URL: www.clinicaltrials.gov.